Improving the policy of public procurements for development of science cities: agent-oriented modeling and scenario analysis - V. I. Abramov (Russian Journal of Economics and Law, 2018)
Objective: to assess the impact of policy change scenarios in the sphere of public procurements on the development of science cities.Methods: simulation modeling, agent-oriented modeling.Results: depressive trends of single-industry towns’ development are one of the key problems in the development of Russia. At the same time, the procedure for identifying suppliers, proposed by the system of public procurements, does not imply mechanisms that would favor the development of science cities. The article analyzes the approaches to estimate the effectiveness of the public procurements system. It is determined that the agent-oriented approach is one of the most promising methods of public procurements management. Through simulation modeling, in particular agent-oriented approach, the article presents the results of scenario experiments. It is established that public procurements can act not only as an instrument of effective expenditure of budgetary funds, but also as a mechanism of economic development of territories. Although the presented experiments showed a decrease in the level of savings as a result of competitive procedures, additional socio-economic effects were achieved, due to the localization of procurements participants in the science cities’ territory. Among other things, the scenarios suggest reduction of transportation costs and, consequently, the traffic flow between Moscow and science cities, which would help to reduce the load on the transport networks of megacities. Scientific novelty: for the first time it was shown that the tool of public procurements can serve for stimulation and maintenance of the development of science cities and single-industry towns and become a key factor in their development. The agent-oriented model of the public procurements system functioning by the example of Zhukovskiy science city was developed, which allows quantitative estimation of the consequences of introducing various mechanisms for improving the procurements activities. The effective method of supporting the procurements participants on a regional basis was experimentally identified and substantiated. Practical significance: the proposed assessment scenarios should be taken into account when forming the normative-regulatory basis in the field of public procurements. The elaborated model allows experimental estimation of invariant scenarios of improving the contract procurement elements, in order to increase the efficiency of the state functions and services, including the efficiency of the budget expenses in the procurements of goods, works, services for providing the state and public needs. The program can be adapted to analyze the functioning of the public procurements system both in other cities and all over Russia.